2016
DOI: 10.1159/000442898
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Synthetic Antimicrobial Peptide GH12 against Oral Streptococci

Abstract: Controlling the growth of cariogenic microorganisms such as oral streptococci is an adjunct therapy for caries-active individuals to prevent and treat caries. Here we investigated the antimicrobial activity of the synthetic amphipathic α- helical antimicrobial peptide GH12 (GLLWHLLHHLLH-NH2) against oral streptococci in vitro. Circular dichroism studies showed that GH12 takes on an α-helical conformation in the presence of membrane-mimicking solvents, and reversed-phase high-performance liquid chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 58 publications
2
45
0
Order By: Relevance
“…More recently, a hydroxyapatite-binding AMP was designed, based on the fusion of specific hydroxyapatite-binding heptapeptide (HBP7) with KSL-W, and this bioconjugate was shown to have improved oral retention and antibacterial efficacy [Huang et al, 2016b]. Other AMPs that have shown in vitro antimicrobial activity against cariogenic bacteria and inhibited oral biofilm formation include a synthetic peptide called L-K6 (derived from the naturally occurring peptide temporin-1CEb), a short synthetic amphiphilic peptide known as 1018, and an amphipathic α-helical peptide containing only 12 amino acids named GH12 [Shang et al, 2014;Wang et al, 2015;Tu et al, 2016].…”
Section: Ecological Approaches To Caries Preventionmentioning
confidence: 99%
“…More recently, a hydroxyapatite-binding AMP was designed, based on the fusion of specific hydroxyapatite-binding heptapeptide (HBP7) with KSL-W, and this bioconjugate was shown to have improved oral retention and antibacterial efficacy [Huang et al, 2016b]. Other AMPs that have shown in vitro antimicrobial activity against cariogenic bacteria and inhibited oral biofilm formation include a synthetic peptide called L-K6 (derived from the naturally occurring peptide temporin-1CEb), a short synthetic amphiphilic peptide known as 1018, and an amphipathic α-helical peptide containing only 12 amino acids named GH12 [Shang et al, 2014;Wang et al, 2015;Tu et al, 2016].…”
Section: Ecological Approaches To Caries Preventionmentioning
confidence: 99%
“…In combat against cariogenic bacteria, our group de novo designed and synthesized a series of cationic, amphipathic α-helical AMPs and selected the most promising one, GH12, a 12-amino acids peptide with optimal structure and potency. Previous studies [20,21] showed that GH12 at the concentration of 8 mg/L, the minimal inhibitory concentration (MIC) and minimal bactericidal inhibitory concentration (MBC) of GH12 against S. mutans , was potent against growth of planktonic bacteria and had a rapid mechanism of action, killing 90% of bacteria in less than 5 min of exposure. Moreover, GH12 effectively inhibited S. mutan s biofilm formation and metabolism, as well as significantly reduced the biomass of 1-day old S. mutans biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…Cytomembrane observation showed that GH12 had a mechanism of killing S. mutans through formation lysis and pores on the cell membrane and envelope. Meanwhile, GH12 had showed little toxic effect on the viability of human gingival fibroblasts [21], and kept stable in human saliva [20]. …”
Section: Introductionmentioning
confidence: 99%
“…Samples were fixed overnight in 2.5% glutaraldehyde solution, dehydrated in graded ethanol solutions, and finally vacuum dried. After being sputter-coated with gold, the samples were observed using a field emission scanning electron microscope (Merlin, Zeiss, Oberkochen, Germany) [Tu et al, 2016].…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…Previous studies have shown that native AMPs isolated from bacteria, fungi, animals, and plants, can have significant bactericidal effects; however, they are expensive to produce and possess potential toxicity [Diamond and Ryan, 2011;Kosciuczuk et al, 2012;Tati et al, 2014]. As a result, modified AMPs have been developed with a lower production cost, a lower host toxicity, and a range of linear or cyclic forms, as well as other forms [Wu and Hancock, 1999;Da et al, 2013;Shang et al, 2014;Tu et al, 2016]. It has also been reported that combinations of a traditional antibiotic and AMPs can be effective as antimicrobial agents against oral pathogens [Lobos et al, 2009].…”
mentioning
confidence: 99%